RELATIONSHIP OF MOTHER'S KNOWLEDGE ABOUT DENTAL HEALTH MAINTENANCE WITH CARIES STATUS IN AL-HIKMAH KIDS OF JAMBI CITY IN 2018 - Sukarsih Sukarsih; Aida Silfia; Sri Febrianti (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2018)
Mother's knowledge about dental health will greatly determine health status of her child's teeth later. Mothers have an important role in their family, as a wife and as a mother. The first figure that is known to the child as soon as he is born is the mother, therefore mother’s behavior and habits can be emulated by child. In the other side, knowledge is not enough to detrmine child dental health, it needs to be followed by commendable attitudes and actions. The Australian dental association has revealed that: "the health of the teeth is the responsibility of his mother". This can be understood because generally the one closest to the child from the age of breastfeeding is his mother. Dental caries is a problem that still not resolved completely in the world. Oral and dental diseases are the most common diseases that experienced by Indonesian people (by 60%). This study aim to determine the relationship of maternal knowledge about maintaining dental health with the status of children’s caries in Al-Hikmah Kindergarten Jambi City in 201. This study can be used to increase further coaching by Jambi Department of Dental Nursing education Ministry of Health. This type of research is descriptive with a cross sectional study design. The study population was the mother and daughter of Al-Hikmah Kindergarten in Jambi City. This study using total sampling population. There are 180 peoples that included in this study which is 90 peoples mothers and 90 peoples children.This study’s hypothesis is the relationship between maternal knowledge about maintaining dental health and caries status in children of Al-Hikmah Kindergarten in Jambi City in 2018. The results of the study showed that mothers with low category of knowledge about maintaining dental and oral health were 53 people (58.9%), while mothers with high category were 37 people (41.1%). Children’s Caries status was 87 people (96.7%) who experienced caries, while there were only 3 caries-free people (3.3%). There is no relationship between the knowledge of mothers about the maintenance of dental and oral health with caries status in children of Al-Hikmah Kindergarten in Jambi City in 2018 with a significance value of 1,000 (p> 0.05).